Membangun Karakter Keluarga Katolik (Kepada Umat Lingkungan) Stasi ST. Yosep Suka Maju, Paroki Tanjung Selamat Medan - Tri Sujarwadi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
The rapid development of technology in the current era of globalization has had a negative impact on the moral development of teenagers. There needs to be an effort made by the adult community to shape the character of the younger generation so that they can recognize their potential. For this reason, as scholars who play a role in the world of education, by looking at the development of the character of the young generation in the current era of globalization, we, the service team, are encouraged to also make our contribution through socialization and training to children, especially ST Station children. Yosep Suka Maju, Tanjung Selamat Parish, Medan, with the activity theme